Estudo da fisiologia de gemas laterais de cana-de-açucar durante o armazenamento - Brambilla, Wilian Polaco [UNESP] (2013)
The present study aimed to characterize the dynamics of the sugar cane buds that when stored at low temperatures and the use of plant growth regulators in order to increase their shelf life during storage. The experiments were conducted in a completely randomized design and the results submitted to variance analysis and means were compared by Tukey test at 5% probability. The work consists of two studies: the first, the buds were stored at low temperatures (4, 8, 12, and 16°C) and high humidity (80%), and harvested at intervals of 3 days (zero to 24 days). The temperature that had higher rates of sprouting at the end of the experiment was 12°C. In the second study, the buds stored at temperature of 12°C were subjected to treatment with benzylaminopurine (BAP) solutions. The application of the plant growth regulator did not affect budburst. Moreover, it was found influences in the activity of antioxidant enzymes